STRATEGIES FOR DEVELOPMENT OF MARKETING INNOVATIONS THROUGH REBRANDING IN COMMERCIAL BANKS (Marketing Journal, 2025)
The article analyzes the role of rebranding in commercial banks in implementing marketing innovations. The importance of rebranding for improving service quality, strengthening customer trust, developing internal management systems, and enhancing competitiveness is highlighted. The analysis concludes that effective rebranding positively affects the overall development of banks. Recommendations for improving banking activities are provided.
Keywords: rebranding; commercial banks; marketing innovation; service quality; competitiveness. 166